Pre-diagnostic leukocyte mitochondrial DNA copy number and skin cancer risk - Meng, Shasha (Carcinogenesis, 2016)
No previous study has examined the association between mitochondrial DNA copy number (mtCN) and skin cancer risk prospectively. We examined the associations between peripheral blood leukocytes mtCN level and the risks of skin cancers in a case–control study nested within the Nurses’ Health Study of non-Hispanic White women, including 272 melanoma cases and 293 controls, 508 squamous cell carcinoma (SCC) cases and 550 controls, and 515 basal cell carcinoma (BCC) cases and 536 controls. Relative mtCN in peripheral blood leukocytes was measured by quantitative PCR-based assay. Unconditional logistic regression models were used to examine the associations between mtCN and skin cancer risks. Compared with those with high mtCN, the risk for melanoma was 1.06 [95% confidence interval (CI) = 0.70–1.62] in the median group and 1.19 (95% CI = 0.78–1.81) for the low group. There was suggestive evidence that increased risk for melanoma was apparent among low constitutional susceptibility group [odds ratio (OR)(low versus high) = 1.80, 95% CI = 0.95–3.39, P for trend = 0.07, P for interaction = 0.06]. The increased risk of melanoma was also apparent among high cumulative UV exposure group (OR(low versus high) = 3.40, 95% CI = 1.46–7.92, P for trend = 0.004, P for interaction = 0.01). For non-melanoma skin cancers, compared with high-mtCN group, low-mtCN group had an increased risk for SCC (OR = 1.26, 95% CI = 0.93–1.71) and BCC (OR = 1.35; 95% CI = 1.00–1.82). Because some of the associations were marginally significant, the results only provided suggestive evidence. Further studies are warranted to replicate these findings and better understand the underlying mechanisms.